A Study On Situational Language Teaching (SLT) In Teaching Vocabulary To The Fourth Year Student At SDN 3 Puro Sragen - Rohmah, Lenny Nur (2008)
This research is conducted to know the implementation of SLT in teaching vocabulary to the fourth year students at SDN 3 Puro Sragen and to discover the strengths and weaknesses of teaching vocabulary using SLT. The writer takes the English teacher and the students of class IV as the subject of the study. The primary data are mainly taken from the observation. The secondary data are obtained from teaching materials and information about the process of teaching vocabulary using SLT. In collecting the data, the writer uses observation and interview. Meanwhile, the data are analyzed by using descriptive qualitative method. After analyzing the data, the writer draws some conclusions. First, the procedure of teaching vocabulary is ESA (Engage, Study, and Activate) procedure. Some activities done in SLT happened in the study and activate session. In the study, the teacher uses some teaching aids and asks the students to repeat the example that she said. Then, in the activate session, the teacher gives some questions to make the students active by answering those questions. Second, there are the strengths and weaknesses of teaching vocabulary using SLT. The strengths are the vocabulary can be learnt easily by using some teaching aids, the students can improve their speaking skill, and the teacher can create situation that's needed by herself. The weaknesses are the students just imitate the teacher, they just depend on the teacher and their pattern of thought can not be improved, the vocabulary learnt is limited by the visual aids, and the students cannot communicate each other.